Impact of Crystal Structure and Particles Shape on the Photoluminescence Intensity of CdSe/CdS Core/Shell Nanocrystals - Ludescher, Lukas; Dirin, Dmity N.; Kovalenko, Maksym V.; Sztucki, Michael; Boesecke, Peter; Lechner, Rainer T. (Frontiers in Chemistry, 2019)
To study the influence of the chemical and crystalline composition of core/shell NCs on their photoluminescence (PL) the mean structural profile of a large ensemble of NCs has to be retrieved in atomic resolution. This can be achieved by retrieving the chemical profile of core/shell NCs using anomalous small angle x-ray scattering (ASAXS) in combination with the analysis of powder diffraction data recorded by wide angle x-ray scattering (WAXS). In the current synchrotron based study, we investigate CdSe/CdS core/shell NCs with different core dimensions by recording simultaneously ASAXS and WAXS spectra. The CdS shells are grown epitaxial on nominal spherical CdSe cores with core diameters from around 3.5 nm to 5.5 nm. Three different CdSe shell thicknesses are realised by depositing around 4, 6 and 8 monolayers (MLs) of CdSe. We reveal that the epitaxial core/shell structure depicts a chemical sharp interface, even after a post growth annealing step. With increasing NC diameter, however, the CdSe/CdS NCs deviate significantly from a spherical shape. Instead an elliptical particle shape with pronounced surface facets for the larger core/shell NCs is found. In combination with the powder diffraction data we could relate this anisotropic shape to a mixture of crystal phases within the CdSe core. The smallest CdSe cores exhibit a pure hexagonal wurtzite crystal structure, whereas the larger ones also possess a cubic zincblende phase fraction. This mixed crystal phase fractions lead to a non-spherical shell growth with different thicknesses along specific crystallographic directions: The long axes are terminated by basal crystal faces parallel either to the a- or c-axis, the short axes by “tilted” pyramidal planes. By combining these structural data with the measured PL quantum yield values, we can clearly connect the optical output of the NCs to their shape and to their shell thickness. Above 6 ML CdS shell-thickness no further increase of the PL can be observed, but for large aspect ratio values the PL is significantly decreased. The gained understanding of the internal crystal structure on CdSe/CdS NCs is general applicable for a precise tuning of the optical properties of crystalline core/shell NCs.